1996
DOI: 10.1161/01.str.27.1.76
|View full text |Cite
|
Sign up to set email alerts
|

Lubeluzole in Acute Ischemic Stroke

Abstract: In patients with acute ischemic stroke, the dosage regimen of 7.5 mg over 1 hour followed by 10 mg/d of intravenous lubeluzole is safe and statistically significantly reduced mortality. Further clinical trials in a larger number of patients are ongoing to confirm efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(29 citation statements)
references
References 6 publications
1
27
1
Order By: Relevance
“…15 Lubeluzole inhibits glutamine rise and glutamine-stimulated rises in cyclic guanosine monophosphate-and nitric oxide-related neurotoxicity. 16 As suggested in the introduction and supported by the results of this study, the circumstances of CPB appear to offer a practical test bed for putative neuroprotective agents. The pathophysiology of massive focal infarction in an embolic stroke and the more diffuse microembolic damage combined with disordered blood flow during CABS are clearly different, so it could not be assumed that efficacy in one context was transferable to the other without a trial in stroke patients.…”
Section: Discussionsupporting
confidence: 63%
“…15 Lubeluzole inhibits glutamine rise and glutamine-stimulated rises in cyclic guanosine monophosphate-and nitric oxide-related neurotoxicity. 16 As suggested in the introduction and supported by the results of this study, the circumstances of CPB appear to offer a practical test bed for putative neuroprotective agents. The pathophysiology of massive focal infarction in an embolic stroke and the more diffuse microembolic damage combined with disordered blood flow during CABS are clearly different, so it could not be assumed that efficacy in one context was transferable to the other without a trial in stroke patients.…”
Section: Discussionsupporting
confidence: 63%
“…5,6 Results of a double-blind, placebo-controlled phase II trial involving 193 patients with acute ischemic stroke showed that lubeluzole, administered intravenously within 6 hours of stroke onset with a 1-hour 7.5-mg loading dose followed by 10-mg/d infusion for 5 days, was safe and resulted in a statistically significant reduction in mortality. 7 In the same study, treatment with a higher lubeluzole dosage regimen of 15-mg loading dose followed by 20-mg/d infusion for 5 days was associated with a higher mortality rate that was attributable, at least in part, to an imbalance at randomization resulting in more patients with severe ischemic stroke being included in the high-dose group. On the basis of the results of this early phase II trial, a dosage regimen of 7.5-mg loading dose administered over 1 hour followed by a continuous infusion of 10 mg/d for 5 days was selected for use in subsequent phase III studies.…”
mentioning
confidence: 96%
“…Lubeluzole shows beneficial efficacy in clinical cases. 30) These results suggest that NHE inhibitors have beneficial efficacy that is as good as other neuroprotective compounds.…”
Section: Discussionmentioning
confidence: 92%